Impact of Sugar Cane Molasses to Concrete Strength and Concrete Retardation - Odal , Algerico Jr. S. (International Journal of Membrane Science and Technology, 2023)
The impacts of sugar cane molasses to the strength and retardation of concrete was investigated in this study. A total of 15 concrete cylinder of size 150mm diameter x 300mm Height with a mix ratio of 1:2:4 were cast with different percentages of sugar cane molasses replacing some proportion of water in the concrete mix. The concrete cylinder was prepared by reducing water by 10-20% with sugar cane molasses in the following percentage, 0.3% by weight of cement of molasses, 0.6% of molasses, 1.2% of molasses and 1.5% of Molasses. The concrete cylinder was cured, tested and the physical properties of concrete were determined. The slump values of the concrete increased by 10mm when the percentage of molasses increases. A decrease in compressive strength was noticed when the percentage of molasses increases. The highest final setting time of 240 minutes occurred at 1.50% of molasses. The increased in retardation of concrete was noticed when the percentages of molasses increases.